2022
DOI: 10.2147/dmso.s376178
|View full text |Cite
|
Sign up to set email alerts
|

Combination of TyG Index and GRACE Risk Score as Long-Term Prognostic Marker in Patients with ACS Complicated with T2DM Undergoing PCI

Abstract: We aimed to investigate the prognostic value of the triglyceride-glucose (TyG) index combined the with Global Registry of Acute Coronary Events (GRACE) score in adult acute coronary syndrome (ACS) patients with type 2 diabetes mellitus (T2DM) who underwent percutaneous coronary intervention (PCI). Methods: The study enrolled total 899 ACS patients with T2DM who underwent PCI. TyG index and the GRACE risk score were calculated and assessed by median. The correlation was analyzed by Spearman's rank correlation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The twenty observational cohort studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] with the total population of1,52,846 (Range: 386-141243)were enrolled between the year 2002 to 2020 with mean age of 59.4 years, published from 2018-2023. A study byZhaiet al 19 reported in-hospital mortality while other nineteen studies had only reported major cardiac adverse eventsat 1 year to 13.2years median time follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…The twenty observational cohort studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] with the total population of1,52,846 (Range: 386-141243)were enrolled between the year 2002 to 2020 with mean age of 59.4 years, published from 2018-2023. A study byZhaiet al 19 reported in-hospital mortality while other nineteen studies had only reported major cardiac adverse eventsat 1 year to 13.2years median time follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the included studies failed to account for statistical differences in smoking between groups. 22,25 Excluding these two trials revealed a significant correlation between the TyG index and post-PCI MACE risk. Due to the limited purview of the research, smoking-specific correlations were not evaluated in this study; therefore, future research is necessary.…”
Section: Discussionmentioning
confidence: 96%
“…The incidence of TyG index and post‐PCI MACE is affected by smoking. Two of the included studies failed to account for statistical differences in smoking between groups 22,25 . Excluding these two trials revealed a significant correlation between the TyG index and post‐PCI MACE risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations